NON-MEDICAL MASKS, SOAKABILITY, IMAGE RECONSTRUCTION, MOISTURE SPREADING AREA OF NON-MEDICAL MASKS - Juwita Gammarika, Manuella
Novel coronavirus or COVID-19 pandemic has demanded global society to change their lifestyle to be more hygienic, one of which is to use masks in public spaces. The public started using mass amounts of medical masks, which caused a shortage supply for medical personnel. Taking that into account, people started to switch from wearing medical masks to non-medical or fabric masks, which thus far have no regulation or testing method standardization. In addition to that, the effectivity of non-medical masks to prevent virus transmission is yet to be decided. One of the most significant criteria for testing masks is soakability or moisture spreading. In this research, a model for non-medical masks testing system is designed, with image-based processing system to obtain data for average velocity of moisture spreading on masks’ surface. System uses calibrated camera for recording and syringe as a manual water apparatus. Image reconstruction is performed using contrast-limited adaptive histogram equalization, mean filter, background subtraction, and morphological segmentation. Different criteria are used to compare types of non-medical masks, which are moisture spreading velocity and suitability of each masks with the suggested system. Data obtained from the experiment showed visual validation as a tool to compare between images from recording and the final correspondent reconstructed images. Average velocity of moisture spreading sequentially for masks from 100% cotton, 100% polyester, and polyester-spandex are 0,92 mm2/s, 0,41 mm2/s, and 0,97 mm2/s, with moisture spreading standard deviation sequentially for each mask 29,5%, 61,3%, and 23,5%.